Trust Networks for Recommender Systems - Victor, Patricia; Cornelis, Chris; de Cock, Martine; SpringerLink (Online service) (Paris : Atlantis Press, 2011)
This book describes research performed in the context of trust/distrust propagation and aggregation, and their use in recommender systems. This is a hot research topic with important implications for various application areas. The main innovative contributions of the work are: -new bilattice-based model for trust and distrust, allowing for ignorance and inconsistency -proposals for various propagation and aggregation operators, including the analysis of mathematical properties -Evaluation of these operators on real data, including a discussion on the data sets and their characteristics. -A novel approach for identifying controversial items in a recommender system -An analysis on the utility of including distrust in recommender systems -Various approaches for trust based recommendations (a.o. base on collaborative filtering), an in depth experimental analysis, and proposal for a hybrid approach -Analysis of various user types in recommender systems to optimize bootstrapping of cold start users.
Keywords: Computer science; Logic design; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; Logic Design